Competition and quality in regulated markets with sluggish demand - Kurt R. Brekke; Roberto Cellini; Luigi Siciliani; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2010)
We investigate the effect of competition on quality in regulated markets (e.g., health care, higher education, public utilities), using a Hotelling framework, in the presence of sluggish demand. We take a differential-game approach, and derive the open-loop solution (providers choose the optimal quality investment plan based on demand at the initial period) and the feedback closed-loop solution (providers observe demand in each period and choose quality in response to current demand). If production costs are strictly convex, the steady state quality is higher under the open-loop solution than under the feedback solution. In both solutions, quality and demand move in opposite directions over time on the equilibrium path to the steady state. While fiercer competition (lower transportation costs or less sluggish demand) leads to higher quality in both solutions, the quality response to increased competition is weaker when players use feedback strategies.
Keywords: H42; I18; I21; L13; L51; 330; regulated markets; competition; quality; differential games; Unvollkommener Markt; Öffentliches Gut; Wettbewerb; Dienstleistungsqualität; Spieltheorie